The Effect of Entrepreneurship Mentoring on Entrepreneurial Intention in the Studentpreneur Corner Program at State University of Surabaya - Saino Saino (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2019)
The purpose of this research is to find out how the mentoring model used and whether entrepreneurship mentoring can increase student entrepreneurial intentions of students who participate in studentpreneur corner programs. The type of research conducted in this study is a quantitative approach. The population in this study was participants from the studentpreneur corner program at the Faculty of Economics, State University of Surabaya (UNESA) with a total of 17 respondents. The data collection technique used was a questionnaire. Data analysis techniques used simple linear regression analysis by using the SPSS 25 program. The results of the research showed that entrepreneurial mentoring had a positive and significant effect on entrepreneurial interest in the studentpreneur corner program. This was indicated by the regression coefficient of 0.404. That is, if entrepreneurship mentoring was carried out by mentors the better, the more positive the impact will be on the increased student entrepreneurial interests who participate in studentpreneur corner programs.